Cannabinoids and Terpenes: How Production of Photo-Protectants Can Be Manipulated to Enhance Cannabis sativa L. Phytochemistry - Desaulniers Brousseau, Vincent; Wu, Bo-Sen; MacPherson, Sarah; Morello, Victorio; Lefsrud, Mark (Frontiers in Plant Science, 2021)
Cannabis sativa is cultivated for its secondary metabolites, of which the cannabinoids have documented health benefits and growing pharmaceutical potential. Recent legal cannabis production in North America and Europe has been accompanied by an increase in reported findings for optimization of naturally occurring and synthetic cannabinoid production. Of the many environmental cues that can be manipulated during plant growth in controlled environments, cannabis cultivation with different lighting spectra indicates differential production and accumulation of medically important cannabinoids, including Δ9-tetrahydrocannabinol (Δ9-THC), cannabidiol (CBD), and cannabigerol (CBG), as well as terpenes and flavonoids. Ultraviolet (UV) radiation shows potential in stimulating cannabinoid biosynthesis in cannabis trichomes and pre-harvest or post-harvest UV treatment merits further exploration to determine if plant secondary metabolite accumulation could be enhanced in this manner. Visible LED light can augment THC and terpene accumulation, but not CBD. Well-designed experiments with light wavelengths other than blue and red light will provide more insight into light-dependent regulatory and molecular pathways in cannabis. Lighting strategies such as subcanopy lighting and varied light spectra at different developmental stages can lower energy consumption and optimize cannabis PSM production. Although evidence demonstrates that secondary metabolites in cannabis may be modulated by the light spectrum like other plant species, several questions remain for cannabinoid production pathways in this fast-paced and growing industry. In summarizing recent research progress on light spectra and secondary metabolites in cannabis, along with pertinent light responses in model plant species, future research directions are presented.